PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM DINAS PERUMAHAN RAKYAT DAN KAWASAN PERMUKIMAN SERTA PERTANAHAN (PERKIMTAN) KOTA PADANGSIDIMPUAN - Juwita Handayani; Edison Siregar; Muhammar Syafii (Yayasan Perguruan Kampus, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are a strategic sector supporting the Indonesian economy, yet they still face challenges in terms of competitiveness, particularly in the era of globalization and technological advancement. This study aims to analyze the application of entrepreneurial management in improving the competitiveness of MSMEs. The method used is a qualitative descriptive approach with simulated data compiled based on general patterns of MSME practices. The results show that the application of entrepreneurial management, such as strategic planning, product innovation, utilization of information technology, and business network development, can increase MSME turnover, market reach, and operational efficiency. Innovation and digital transformation, including the use of social media and e-commerce, are key factors in strengthening the position of MSMEs in the market. However, obstacles such as limited capital, low digital literacy, and conventional mindsets remain major barriers. Therefore, synergy is needed between the government, academics, and business actors to build an adaptive and sustainable entrepreneurial ecosystem in Padangsidimpuan City.